Dogmatic assessment of the (in)adequacy of insignificance in complex crimes (Revista do Tribunal Regional Federal da 3ª Região, 2021)
This academic article is aimed at studying the hermeneutic criterion of insignificance and its projection with regard to complex crimes, formulating objections and pointing out contributions, with the purpose of establishing a solid framework for this discussion. In order to ensure coherence in the final conclusion, this study ends its program by addressing the epistemological evolution of criminal dogmatics, reaching the edification of functionalism, as well as the fundamental function of Criminal Law, also bringing conceptual and developmental considerations about the criminal-legal good. Finally, a favorable scenario has been formed for the nuances of the subject to be examined, with the aim of determining the dogmatic path best suited to understanding and resolving this issue, which is highly relevant in the context of the analysis of criminal typicality.
Keywords: Dogmatics; typicality; functinalism; minimal criminal intervention; insignificance; complex crimes